Information Visualisation quadrant display. A synergistic approach to a postgraduate program - Botelho, M.C.; Vilar, E.; Cardoso, E.; Alexandrino da Silva, A.; Almeida, P.; Rodrigues, L.; Pinto-Martinho, A.; Rodrigues, S. (Data Science, Statistics & Visualisation (DSSV 2017), 2017)
Information visualization (Infovis) has become a privileged medium of mass visual communication [1]. The multidisciplinary nature of information visualization is today fairly consensual in both professional and academic communities. It is organized around four articulated areas - information design, data visualization, visual analytics, and data journalism that operate within the information visualization domain. Infovis is increasingly becoming an independent research eld with a speci c research agenda [2], seeking to provide people with better and more effective ways to understand and analyse datasets. This multidisciplinary approach and the profuse discussions about the teaching methods for Information Visualization are the foundation of a postgraduate program, which brings together two universities and three schools (in the areas of Social Studies, Design and Technologies). This poster aims to contribute to a much needed and current debate on Information Visualization, considering four main areas. It also contributes to an innovative quadrant display, since it summons and discusses the multiple viewpoints of the four areas as well as the bridges between them. The connections between the four main areas are visually represented through a metaphor referring to the children's game the cootie catcher. Each time a triangle is opened, an areas perspective is revealed, as it is also revealed its interaction with the others. These interactions or bilateral synergies enable deeper reflections on which contents should be present for the different curricular units. It is concluded that, even if there are speci cities in each area, a common language may be adopted and synergies may be generated. The debate on the matter will continue and new challenges will certainly arise upon the implementation of the postgraduate program. [1] P. A. Hall (2011) Bubbles, lines and string: How visualization shapes society, in Graphic Design Now in Production, Blauvelt, A. & Lupton, Eds, USA: Walker Art Center, 170{185. [2] D. Keim, J. Kohlhammer G. Ellis, and F. Mansmannn (2010) Mastering the information age: solving problems with visual analytics. Eurographics Association: Goslar, Germany.